MENINGKATKAN KEMANDIRIAN BELAJAR MATERI RESPON INTERNASIONAL TERHADAP KEMERDEKAAN INDONESIA MELALUI METODE KLOS - Aisha Akuba (Jambura History and Culture Journal, 2023)
This research was carried out to increase the independence of students in the process of learning history in class XII IPS SMAN 1 Tapa. Techniques to increase independence with the KLOS method. The KLOS method is used by providing learning materials in the form of incomplete discourses or readings. Certain parts are omitted with the aim of independent learners in the learning process. The results of classroom action research carried out for two cycles on students of class XII IPS SMAN 1 Tapa showed a change in the independence of students in the learning process in class. Based on cycle I and cycle II data, it is clear that there is an increase in students independence in the learning process in class XII IPS SMAN 1 Tapa. This is seen in all aspects in cycle I and then increases in cycle two. The results of the study clearly show that the KLOS method can be used as one of the techniques to increase the independence of studentsin the process of learning the history of international respons material to Indonesian independence